Cytomorphological changes in breast carcinomas, after neoadjuvant chemotherapy: a study of twenty cases - Pasam, Ramana Kumari; TV, Sivarama Krishna; MG, NagaKishore (International Journal of Research in Medical Sciences, 2017)
Background: Neoadjuvant chemotherapy administered pre-operatively is the standard of care therapy for locally advanced breast cancers, mainly for clinical down staging. The histopathological evaluation of tumor response is the gold standard. Aims: To study the morphological changes induced with neoadjuvant chemotherapy in breast carcinoma and assess the response or non-response of cancers to systemic therapy, based on a web based calculation script at www.mdanderson.org/breastcancer_RCB and also evaluated basing on NSABP-B18 system. Methods: 20 cases of radical mastectomies in locally advanced breast carcinomas with neoadjuvant chemotherapy are studied. Results: All the cases are female breast cancers. Macroscopically, the size of the tumor bed ranges from 10 mm to 90 mm in maximum dimension. The morphological changes: Tumor cellularity, cytomorphological changes. In the present study 20% of cases are pCR/RCB 0, 40% are pNR/RCB III cases and 40% are pPR/RCB I & II (i.e. pCR- pathological complete response, pNR-pathological no response, pPR-pathological partial response, RCB-Residual Cancer Burden). Conclusions: The spectrum of changes observed in the tumor bed is coagulative necrosis, hyalinisation, dystrophic calcification and intense mononuclear inflammatory cell collections, cytoplasmic vacuolization and bizarre nuclei. Quantification of the residual disease by RCB system and to categorize the residual disease is important, to predict the disease-free relapse rate.